AB0520 FIVE-YEAR RATE OF HOSPITALIZATIONS IN ANCA-ASSOCIATED VASCULITIDES IN THE ITALIAN REGION OF FRIULI VENEZIA GIULIA (2013-2017). (13th June 2020) - Quartuccio, L.; Treppo, E.; De Vita, S.; Valent, F.
Abstract : Background: ANCA-associated vasculitides (AAV) are a group of systemic vasculitis carrying a high risk of hospitalization because the multiorgan involvement, the acute nature of some clinical manifestations, the chronic but very disabling course of some other manifestations and finally the risk of severe infections due to chronic glucocorticoid and immunosuppressor administration. However, data on hospitalization due to ANCA-associated vasculitis are still scarce. Objectives: to estimate the rate of the first hospitalization or the death in patients suffering from AAV in the Italian region of Friuli Venezia Giulia (about 1, 200, 000 inhabitants) from year 2013 to 2017. Methods: integration of the information coming from many administrative databases were used to this end. The Regional Health Information System of Friuli Venezia Giulia was used as the source of information for this retrospective cohort study. The system covers the entire regional population and includes various electronic health administrative databases that can be linked with one another on an individual basis through a unique encrypted identifier. In particular, the following databases were matched: the database of the regional potential health care beneficiaries (including demographic information and the residential history of all of the subjects living in the region), the hospital discharge database, the database of exemptions from medical charges were used for this study, the database of the different regional laboratories. The population under study was selected based on the following inclusion criteria: patients were residents in Friuli Venezia Giulia and they had to carry the exemption code for AAV, including Granulomatosis with Polyangiitis (GPA), or Eosinophilic Granulomatosis with Polyangiitis (EGPA), or Microscopic Polyangiitis (MPA). This population was observed from 2013 to 2017. The coded event was the occurrence of the first hospitalization or the death. Also, all the hospitalization and their main discharge diagnoses were registered. Results: 103 patient with AAV were identified. The number of patients with at least one hospitalization/death was 74/103 (71, 8%). Seven patients died during the observation period (6, 6%). The whole number of hospitalizations was 285 in 74 patients. 55/74 (74, 3%) patients experienced more than one hospitalization. In the majority of the hospitalizations (119/285, 41, 7%), the cause of hospitalization was directly attributable to the disease itself, while the second cause of hospitalization was the infections (26/285, 9, 1%). In 10/103 patients (9, 7%), an end stage renal disease was recorded as event. The presence of at least one positivity for ANCA antibodies was documented in 76/103 patients (73, 8%), mainly in patients carrying GPA. Globally, the presence of ANCA antibody seems to be associated with greater likelihood of an event (p=0, 07, log-rank test). The first event occurred in 50% of ANCA-positive patients within 180 days from diagnosis, while in 50% of ANCA negative patients in 859 days. 6 out of the 7 deaths occurred in ANCA positive patients. Conclusion: the rate of hospitalization in AAV is very high confirming the high health care burden of illness. The disease itself is often the cause of the hospitalization, as well as the infectious complication, highlighting the need for more effective treatments, and glucocorticoid sparing therapies. ANCA antibody may represent a biomarker of a more serious disease. Disclosure of Interests: Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Elena Treppo: None declared, Salvatore De Vita Consultant of: Roche, GSK, Speakers bureau: Roche, GSK, Novartis, Francesca Valent: None declared